Kristapurāṇa: Reshaping Divine Space - Eliasson, Pär (Journal of Hindu-Christian studies, 2017)
If a place is simply a physical location, the word space can be used for something shaped by mental processes. Physical places influence our lives by putting limits to the physically practicable, whereas spaces exercise their influence through mental processes like shaping our beliefs, values and sentiments. A space may be a mental superstructure based on an actual place, but, since its power is mental, it is not necessary that this place physically exists. One such space, with power to affect the lives of human beings, is heaven. Belief in heaven has had and still has great impact on many people's thinking and acting. Heaven can be regarded as a part of a more general conceptual space inhabited by (ideas of) the divine and/or spiritual. I will refer to this as divine space.